When does it hurt? The exchange rate pain threshold for German exports - Ansgar Belke; Matthias Goecke; Martin Guenther (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper deals with the impact of the / exchange rate on German exports in the period from 1995Q1 to 2008Q4. Our main aim is to identify pain thresholds for German exporters. We rely on a non-linear model according to which suddenly strong spurts of exports occur when changes of the EXR go beyond a kind of play area (analogous to a mechanical play). We implement an algorithm describing play-hysteresis into a regression framework. A unique pain threshold of the / exchange rate does not exist, since the borders of the play area and, thus, also the pain threshold (as the upper border) depend on the historical path of the whole process. We come up with an estimate of a play area width of 24 US dollar cent per euro. At the end of our estimation period, the previous exchange rate movements had shifted the upper bound of the play area to about 1.55 US dollar per euro. In our interpretation, this is the current pain threshold, where a strong spurt reaction of exports to a further appreciation of the euro is expected to start.
Keywords: C51; C63; E24; F41; 330; Exchange rate movements; play hysteresis; modelling techniques; switching regression; export demand; US-Dollar; Wechselkurs; Volatilität; Außenhandelswirtschaft; Exportindustrie; Export; Nachfrage; Schätzung; Deutschland